Ciprofloxacin Release Using Natural Rubber Latex Membranes as Carrier - Murbach, Heitor Dias [UNESP]; Ogawa, Guilherme Jaques [UNESP]; Borges, Felipe Azevedo [UNESP]; Miranda, Matheus Carlos Romeiro [UNESP]; Lopes, Rute [UNESP]; Barros, Natan Roberto [UNESP]; Mazalli, Alexandre Vinicius Guedes [UNESP]; Silva, Rosangela Gonçalves da [UNESP]; Cinman, José Luis Ferreira [UNESP]; Drago, Bruno de Camargo [UNESP]; Herculano, Rondinelli Donizetti [UNESP] (Hindawi, 2014)
Natural rubber latex (NRL) from Hevea brasiliensis is easily manipulated, low cost, is of can stimulate natural angiogenesis and cellular adhesion, is a biocompatible, material and presents high mechanical resistance. Ciprofloxacin (CIP) is a synthetic antibiotic (fluoroquinolone) used in the treatment of infection at external fixation screws sites and remote infections, and this use is increasingly frequent in medical practice. The aim of this study was to develop a novel sustained delivery system for CIP based on NRL membranes and to study its delivery system behavior. CIP was found to be adsorbed on the NRL membrane, according to results of energy dispersive X-ray spectroscopy. Results show that the membrane can release CIP for up to 59.08% in 312 hours and the mechanism is due to super case II (non-Fickian). The kinetics of the drug release could be fitted with double exponential function X-ray diffraction and Fourier transform infrared (FTIR) spectroscopy shows some interaction by hydrogen bound, which influences its mechanical behavior.
Keywords: ciprofloxacin; natural rubber; Drug Delivery System; biomembranas